The effect of training on aerobic power characteristics of young cross-country skiers. - Rusko, H. (Journal of Sports Sciences, 1987)
Intensive training at anaerobic threshold or higher is the most effective method for improving VO2max. Low-intensity continuous training is a better method for improving anaerobic threshold.